The Averaged EMGs Recorded from the Arm Muscles During Bimanual “Rowing” Movements - Tomiak, Tomasz; Gorkovenko, Andriy V.; Tal'nov, Arkadii N.; Abramovych, Tetyana I.; Mishchenko, Viktor S.; Vereshchaka, Inna V.; Kostyukov, Alexander I. (Frontiers in Physiology, 2015)
The main purpose was to analyze quantitatively the the average surface EMGs of the muscles that function around the elbow and shoulder joints of both arms in similar bimanual ‘rowing’ movements, which were produced under identical elastic loads applied to the levers (‘oars’). The muscles of PM group (‘pulling’ muscles: elbow flexors, shoulder extensors) generated noticeable velocity-dependent dynamic EMG components during the pulling and returning phases of movement and supported a steady-state activity during the hold phase. The muscles of RM group (‘returning’ muscles: elbow extensors, shoulder flexors) co-contracted with PM group during the movement phases and decreased activity during the hold phase. The dynamic components of the EMGs strongly depended on the velocity factor in both muscle groups, whereas the side and load factors and combinations of various factors acted only in PM group muscles. Various subjects demonstrated diverse patterns of activity redistribution among muscles. We assume that central commands to the same muscles in two arms may be essentially different during execution of similar movement programs. Extent of the diversity in the EMG patterns of such muscles may reflect the subject’s skilling in motor performance; on the other hand, the diversity can reflect redistribution of activity between synergic muscles, thus providing a mechanism directed against development of the muscle fatigue.